Исследование вибрационных характеристик опорной конструкции длинного валопровода - Красников, Сергей Васильевич (НТУ "ХПИ", 2006)
The problems, related with creation of test bed for lengthy rotor-system are considered. On the basis of the eigentones analysis of a several versions of a rotor-base system guidelines on a construction of the test bed are made. The mathematical models and calculations are executed on the basis of finite elements method
Keywords: проектирование; рамная конструкция стенда; диск компрессора; частота вращения валопровода; фундамент